A multi-omics approach reveals molecular mechanisms by which phthalates induce cardiac defects in zebrafish (Danio rerio). (October 2020) - Mu, Xiyan; Chen, Xiaofeng; Liu, Jia; Yuan, Lilai; Wang, Donghui; Qian, Le; Qian, Yu; Shen, Gongming; Huang, Ying; Li, Xuxing; Li, Yingren; Lin, Xiangming
Abstract: The potential risks of phthalates affecting human and animal health as well as the environment are emerging as serious concerns worldwide. However, the mechanism by which phthalates induce developmental effects is under debate. Herein, we found that embryonic exposure of zebrafish to di-(2-ethylhexyl) phthalate (DEHP) and di-butyl phthalate (DBP) increased the rate of heart defects including abnormal heart rate and pericardial edema. Changes in the transcriptional profile demonstrated that genes involved in the development of the heart, such as tbx5b, nppa, ctnt, my17, cmlc1, were significantly altered by DEHP and DBP at 50 μg/L, which agreed with the abnormal cardiac outcomes. Methylated DNA immunoprecipitation sequencing (MeDIP-Seq) further showed that significant hypomethylation of nppa and ctnt was identified after DEHP and DBP exposure, which was consistent with the up-regulation of these genes. Notably, hypermethylation on the promoter region (<1 kb) of tbx5b was found after DEHP and DBP exposure, which might be responsible for its decrease in transcription. In conclusion, phthalates have the potential to induce cardiac birth defects, which might be associated with the transcriptional regulation of the involved developmental factors such as tbx5b . These findings would contribute to understand the molecular pathways that mediated the cardiac defects caused by phthalates. Graphical abstract: Image 1 Highlights: DEHP and DBP possess the ability to induce cardiac defect towards zebrafish. Genes involved in heart development were altered by 50 μg/L DEHP and DBP. The promoter hypermethylation of tbx5b may contribute to the heart defect caused by phthalates. Abstract : DEHP and DBP induced cardiac defects toward zebrafish embryos through transcriptional and DNA methylation change of involved regulators.